Bridging the funding gap for public sector investment projects: a case of the department of Agriculture, technical and extension services (Agritex). - Twamba, Owen (Midlands State University, 2015)
The need to provide adequate and equitable housing has remained a major priority for every government while facilitating homeownership has always been a key component of housing policies generally. The study was aimed at investigating the impact of inadequate funding of Public Sector Investment Projects (PSIP), particularly staff houses using a case study of the Department of Agriculture Technical and Extension Services (Agritex). Evidence highlighted that Agritex started on some PSIP projects in 2010 across the eight provinces to construct staff houses but the projects has not been completed due inadequate financial resources. Thus, the objectives were; to establish the impact of insufficient funding of the PSIP projects, to examine the causes of the limited financial resources, to analyze possible strategies that can be implemented to address the funding challenges and to make recommendations on alternative sources of funding of the projects as well as on how best can the department of Agritex can improve revenue generation. The study adopted the use of the case study research method. Though the issue of inadequate was evident in many public institutions that depend on budget resources, Agritex was representative enough to be a case study. Furthermore, the researcher was part of Agritex and access to information was easier. The study population was restricted to 4 top management, 6 Human Resources personnel, 7 Finance and Accounts Staff, 3 Administration Staff and 19 Extension Specialists. The researcher adopted the use of questionnaires and interview. The study noted that housing play an important role in economic development and growth despite it being a basic need for everyone. The study also noted that, Agritex has a backlog in terms of providing accommodation to its members while low capacity utilization by the major economic sectors and budget constraints were identified as the major causes of inadequate financial resources. The study highlighted that structural reforms were needed in the country to encourage trade, and investment. The study however, recommends the department of Agritex to adopt the Public Private Partnership (PPP) arrangements, engage the donor community for funding of projects, development of housing schemes and investment promotion activities in order to attract foreign direct investments so as to ensure that the housing project is fully supported and funded.